Analytic and continental philosophy: methods and perspectives : proceedings of the 37th International Wittgenstein Symposium - Rinofner-Kreidl, Sonja; Wiltsche, Harald A. (Publications of the Austrian Ludwig Wittgenstein Society, 2016)
Frontmatter -- Table of Contents -- Introduction -- Can You Have My Pain? -- Wittgenstein’s On Certainty and Relativism -- Wittgenstein and Free Will -- Wittgenstein’s Last Writings -- Analytic and Continental Philosophy: From Duality Through Plurality to (Some Kind of) Unity -- For Analytic Phenomenology -- Towards a New Foundationalist Turn in Philosophy: Transcending the Analytic-Continental Divide -- Two Phenomenological Accounts of Intuition -- Imagination and 4E Cognition: An Analytic-Continental Exchange -- Intuition und Argumentation – zum Verhältnis von intuitiver und diskursiver Vernunft -- Truth against Reason, and Reason against Truth -- Don’t beep me, bro’! – A Worry About Introspection -- Metaphysical and Phenomenological Perspectives on Habituality and the Naturalization of the Mind -- Embodied Knowledge – Embodied Memory -- Panpsychism in the First Person -- What Is It Like to Be an Angel? -- Do Group Persons have Emotions – or Should They? -- Collective Intentionality and the Collective Person in Max Scheler -- Being Well Together – Aristotle on Joint Activity and Common Sense -- Pretence and the Inner. Reflections on Expressiveness and the Experience of Self and Other -- Socialization, Reflection, and Personhood -- ‘Vaulting Ambition’ – Machiavelli’s Emtpy and Impure Concepts -- The Distinction between Objective and Subjective Standards in the Criminal Law -- Gibt es einen kantianischen Intuitionismus in der Ethik? -- Sensibility and Values Toward a Phenomenological Theory of the Emotional Life -- Stolz und Vorurteil. Über einige Schwierigkeiten der ethischen Selbstbewertung -- Index of Names -- Index of Subjects
Keywords: Konferenzschrift -- 2014 -- Kirchberg am Wechsel; Sozialphilosophie; Ethik; Philosophy of Mind; Analytische Philosophie; Wittgenstein, Ludwig